Resilience of small-scale farmers amidst the COVID-19 Pandemic: a case study of small-scale farmers in Limpopo Province, South Africa - Ramarumo, Thanyani (Graduate School of Business (GSB), 2026)
This qualitative study examines the impact of COVID-19 lockdowns on small-scale farmers in Limpopo, South Africa. The closure of various market channels such as street vendors, restaurants, hotels and large social gatherings by the government left these farmers susceptible to market shocks, given their reliance on these channels. Over a span of 17 months, the study observed 21 farmers, exploring their adaptive strategies amidst the crisis. Farmer selection was based on their access to various markets: municipal markets, local informal markets, or alternative channels facilitated by intermediaries. The research underscores a pronounced correlation between market access and resilience. Farmers with market access demonstrated greater resilience compared to their counterparts lacking such access. The study further details the various coping mechanisms adopted by these farmers, including finding alternative markets, starting new businesses, changing crop patterns, and modifying their transport system. This research provides a deeper understanding of the intricate link between market access and farmer resilience, particularly for small-scale farmers facing both supply and demand disruptions. Furthermore, the study highlights that intermediaries can play a crucial role in strengthening farmers' resilience during crises. However, their effectiveness is dependent on the organisation's vision and goals. It also provides practical implications for improving market access and government response to crises. This includes government preparedness for similar future disruptions can be achieved by collaborating with the private sector to establish localised markets in rural communities. Also prioritising the development of these local markets is essential for bolstering both local food systems and farmers' resilience in the face of the shocks.